Religiosity as the moderating effect of diamond fraud and personal ethics on fraud tendencies - Istifadah, Rikyan Ulil; Senjani, Yayu Putri (Journal of Islamic Accounting and Finance Research, 2020)
Purpose - This study aims to determine the effect of each dimension of diamond fraud (pressure, opportunity, rationalization, capability) and personal ethics on the fraud tendency (assets misappropriation) and understanding of religiosity as moderating variable.Method - The study was conducted by survey method. The samples are amil zakat in Yogyakarta. Data analysis in this study applied multiple linear regression analysis with IBM SPSS version 22. The instruments were adopted from previous research.Result - The results of data analysis in this study show that there are positive influences between elements of diamond fraud (pressure, opportunity, rationalization, capability) on the fraud tendency (assets misappropriation) but personal ethics do not influence the fraud tendency. While the understanding of religiosity is able to moderate elements of diamond fraud (pressure, opportunity, rationalization, capability) and personal ethics.Implication - Future research can expand the object of research in several other provinces. In addition, fraud theory used is Fraud Diamond Theory. Whereas now there has been an increase in the cause of fraud, which is arrogance and evolved into Fraud Pentagon Theory, so that the next arrogance variable can be added as an independent variable.Originality - This reseacrh is still using samples in one province, and Amil Zakat sample was chosen as a sample because based on data submitted by BAZNAS.